TIDAL RANGE CALCULATION BASED ON THE LOCAL KNOWLEDGE OF THE SAMA ETHNIC GROUP IN THE EASTERN INDONESIA - . Salnuddin; I Wayan Nurjaya; Indra Jaya; Nyoman M.N. Natih (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2015)
The Sama ethnic group (Bajo) is well known as “Indonesian marine people” that dominantly spreaded in coastal region of eastern Indonesian region. Their activities have been adapting with the territorial water as shown in the determination of their home floor height to prevent from the tidal flood. The purpose of this study was to examine the accuracy of the tidal range calculation by local knowledge of the Sama ethnic group (Sama Ethnic Method, SEM). The analysis was done by comparing tidal range result calculated by the Sama Ethnic Method (SEM) with the standardized tidal harmonic constituents.  The result showed that the 2nd tidal peaks (DLB-s) in the 15th “Sya’ban” date was the best date to do measurement of a tidal range. In this case, the “Likkas Silapas” (LS) value at the above date was above the mean height water level (MHWL). Meanwhile, in other dates, the LS value was under MHWL value. The result also showed a strong correlation (R2> 90%) between rasio of tidal high on 1st and 2ndpeaks (DLB-s/DLB-m) on 15th Sya’ban date and LS-s value. The local knowledge of the Sama Ethnic Method to determine the tidal range was effective and scientifically proven. Keywords: the Sama Ethnic group, tidal range, Likkas Boe, Likkas Silapas, Sya’ban